Biologia reprodutiva do opilião Iporangaia pustulosa (Arachnida: Opiliones): seleção sexual e evolução do cuidado paternal - Santos, Gustavo Requena (2008)
Exclusive paternal care is rare reproductive strategy that and has evolved only in the order Opiliones among arachnids. Although nearly half of the independent events of evolution of this behavior in arthropods has occurred in the order Opiliones, only a few studies have investigated in detail the reproductive biology of harvestmen species. Iporangaia pustulosa is a harvestman endemic of the Atlantic Forest that lives on the vegetation and whose females leave their eggs under the exclusive guard of the males. The main goals of this work were to describe the reproductive biology of Iporangaia, to quantify the costs and benefits of paternal behavior, and to test all predictions of the hypothesis of evolution of paternal care via sexual selection using this harvestman species as model organism. The fieldwork was done between July 2003 and January 2007, in two transects (200 m and 600 m length) alongside a river that follows the Caçadinha track at the Parque Estadual Intervales, SP. Fieldwork included naturalistic observations allied to field experiments and a one year capture mark recapture study. The observational data generated descriptions of the reproductive biology of Iporangaia and were used in null models and model selection analysis. The reproductive activity of the population was not restricted to a specific season, with individuals reproducing throughout the year. Paternal care is crucial to assure offspring survival, since males aggressively defend the eggs against predators. Furthermore, eggguarding seems to be exhibited by males as a sexual display to females, increasing males attractiveness, since the more time males stay on their egg-batches, the more number of eggs are added to their clutches. Egg-guarding behavior affects male survival, but, contrary to what would be expected by the theory, caring males presented higher survival rates when compared to non-caring males and females. Assuming that predation is the process leading to this differences, one can speculate that, given that non-caring males and females present greater displacements than caring males, they are more exposed to ambush predators, which are the main harvestmen predators in the study area. Finally, the results support all predictions of the hypothesis of evolution of paternal care via sexual selection, except to the fact that non-caring males do not guard unrelated eggs. Iporangaia pustulosa is one of the few paternal species that have its reproductive biology studied for a long period and the information obtained here indicates that male care in this species presents exceptionally low costs related to the high benefits to the caring males.